Development of multi-epitope Cathepsin L driven short peptide vaccine against Fasciola gigantica - Chansap, Supanan; Cheukamud, Werachon; Suthisintong, Thitikul; Kueakhai, Pornanan; Changklungmoa, Narin (Frontiers in Veterinary Science, 2025)
Fasciolosis is an important zoonotic disease caused by Fasciola species (Fasciola spp.). Fasciola spp. infection has the potential to affect the livestock economy. Furthermore, liver flukes have been found to present Triclabendazole resistance in many countries. Vaccines are used to prevent fasciolosis and are currently considered the best alternative. However, no liver fluke vaccine is commercially available at present. Fasciola gigantica Cathepsin Ls (FgCatLs) are vital enzymes for the liver fluke’s survival. Therefore, this study aimed to design and investigate the immune response of multi-epitope Cathepsin L (MeCatL) driven short peptide vaccine for fasciolosis using immunoinformatic tools. FgCatLs sequences were predicted Linear B cell (BCL)- and Helper T lymphocyte (HTL)-specific immunogenic Eepitopes. The selected epitopes were marked on FgCatL’s alignments. Novel epitopes were constructed from three criteria, including the selection process taking non-conserved host regions, overlapping FgCatLs sequences, and the highest percent conserved residues. Novel epitopes of BCL and HTL were linked with a linker to design a short peptide. MeCatL driven short peptide presented high antigenicity, non-allergenicity, non-toxicity, and good solubility. MeCatL driven short peptide was predicted and refined the tertiary structure. The refined MeCatL driven short peptide model indicated good quality structure that was investigated by Ramachandran plot, ERRAT, and Z-score. The refined MeCatL driven short peptide model interacted with Toll-like receptor 2 (TLR-2). The lowest energy was −1222.4 kJ/mol. The levels of IgM, IgG1, and IgG2 were increased in in silico immune simulation. MeCatL driven short peptide was synthesized and immunized in mice. IgG1 and IgG2a levels were increased after week 2, indicating IgG1 levels were dominating. MeCatL driven short peptide immunized sera can detect single proteins, including rFgCatL1, rFgCatL1G, and rFgCatL1H. In addition, MeCatL driven short peptide immunized sera was specifically detected in the cecal epithelium of NEJ and adult stages. These findings suggest that the MeCatL short peptide is a promising vaccine candidate, capable of inducing targeted immune responses, though further studies are needed to confirm its protective efficacy in vivo.